Insilico analysis of hypothetical proteins unveils putative metabolic pathways and essential genes in Leishmania donovani - Ravooru, Nithin; Ganji, Sandesh; Sathyanarayanan, Nitish; Nagendra, Holenarsipur G. (Frontiers in Genetics, 2014)
Leishmaniasis is a parasitic disease caused by the protozoan Leishmania, which is active in two broad forms namely, Visceral Leishmaniasis (VL or Kala Azar) and Cutaneous Leishmaniasis (CL). The disease is most prevalent in the tropical regions and poses a threat to more than 70 countries across the globe. In the Indian subcontinent, about 200 million people are estimated to be at risk of developing VL and this area harbours an estimated 67% of the global VL disease burden. The state of Bihar alone has captured almost 50% of the total cases in the Indian region. While no vaccination exists, several pentavalent antimonials and drugs like Paromomycin, Amphotericin, Miltefosine etc., are used in the treatment of Leishmaniasis. However, due to low efficacy of these drugs and the resistance developed by the bug to these medications, there is an urgent need to look into species specific targets. The proteome information available suggests that among the 7960 proteins, a staggering 65% of it remains to be annotated with clarity. Hence, in the present study, we have demonstrated a protocol to integrate the seqeunce and functional information from various databases, such as GO, PFAM, KEGG, String DB, COG and DEG, to assign putative functions to many of the hypothetical seqeucences present in this proteome. These crucial information related to pathways and essential genes show promise for exploring the design strategies towards developing drugs, to tackle this notorious parasitic disease.